Assessing The Teaching Quality of Physical and Health Education Teachers in Junior Secondary Schools in Lagos State Nigeria - ADEGBAMIGBE, Adesulue Babalola; AIYEJUYO, Lanre Joseph; AYOADE, Timothy Olusoji; OKESANYA, Adeyemi Taoheed; LAJIDE, Emmanuel Oluranti; ELESO, Timothy Taiwo; ADESANYA, Adeyemi Taofik; ASIKHIA, Toyin Funmi (late); BLAVO, Jude Femi (International Journal of Holistic Health, Sports and Recreation, 2023)
The quality of teaching has become a prominent issue in the area of physical and health education due to the new trends in teaching pedagogy, assessment, aids, modes and the content of the curriculum. However, the teaching quality of physical and health education can be determined using co-variates such as the curriculum content knowledge, reflections and subject status. This study therefore assessed the teaching quality of Physical and health education Teachers in Junior Secondary School in Lagos State, Nigeria. The study adopted the descriptive survey research design. All the Junior Secondary Schools in Education District IV consisting of Apapa, Surulere and Mainland Local Government Areas were covered in the study. Two hundred and thirty-Five Physical and health education Teachers were purposively sampled for the study. A standardized questionnaire with reliability co-efficient of 0.83 was used as an instrument to collect data for the study. Three hypotheses were tested at 0.05 level of Significance. Data collected were subjected to frequency counts and percentages and inferential statistics of chi-square. The study established that two of the hypotheses were rejected except for one, and eleven respondent’s mortality was recorded in the study. There was a significant influence of the co-variates on the teaching quality of physical and health education in junior secondary schools in education district IV. it is therefore recommended that among others that upgrading teacher’s knowledge or physical and health education will be an added advantage of the subject and this can be achieved by internship trainings and courses in other to maintain a standard level.